Audit Quality, Firm Size, and Leverage as Determinants of Going Concern Opinions: Evidence from the Financial Sector (2018–2022) - Albab, Farah Nisa Ul; Chairani, Yusmanita; Indriastuti, Mila (E-Jurnal Akuntansi; Vol 34 No 11 (2024)DO - 10.24843/EJA.2024.v34.i11.p16, 2024)
A going concern audit opinion is issued by independent auditors when substantial doubt exists regarding a company's ability to continue its operations within a specified period following the issuance of the audit report. This study employs quantitative research methods and relies on secondary data. The research involves document analysis, including a review of prior studies and the examination of documents relevant to the research objective. The data comprises annual financial reports spanning a five-year period (2018–2022), yielding 73 observations selected through purposive sampling. Logistic regression analysis was employed to evaluate the relationships among the variables. The findings reveal that company size negatively influences the issuance of a going concern audit opinion. In contrast, audit quality and leverage exhibit no significant effect on the likelihood of a going concern audit opinion being issued.